(untitled) (Texas Journal of Philology, Culture and History, 2024)
The article is dedicated to the study of the history of abbreviations in the Russian language. Various types of abbreviations, their classifications, and evolution are considered. Special attention is paid to the works of Russian and foreign researchers, as well as scientists from the CIS and Uzbekistan. Key trends in the use of abbreviations and problems associated with their application are analyzed. The results of the study emphasize the importance of abbreviation for saving language resources and simplifying communication in the context of the development of information technologies. The prospects for further research and recommendations for the use of abbreviations in various contexts are discussed